2023
DOI: 10.4103/jips.jips_354_22
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of titanium dioxide nanoparticles and silver nanoparticles for flexural strength once incorporated in heat-cure acrylic denture base resin: An in vitro Study

Abstract: Aim: Polymethylmethacrylate (PMMA) resin is the most by and large used denture base material. Denture fractures are sequential to the flexure or impacting forces. Different nanoparticles such as titanium dioxide and silver nanoparticles have been used to improve its antimicrobial properties. There are limited data on their effect on flexural strength. The aim of the study was to assess the effect of silver nanoparticles and titanium dioxide nanoparticles addition on flexural strength of PMMA resin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…Other studies [40,41] found opposite results of a decreased FS with the addition of TNPs. Pai et al [56] added TNPs at different concentrations of 0.5%, 1%, 2%, and 3% and found that the flexural strength of PMMA decreased with the addition of TNPs with a gradual decline with increasing concentrations of nanoparticles. In contrast, the study by Bdelraouf et al [57] showed an increase in the FS with 5% TNPs, which may be due to the resin type used: autopolymerized resin.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies [40,41] found opposite results of a decreased FS with the addition of TNPs. Pai et al [56] added TNPs at different concentrations of 0.5%, 1%, 2%, and 3% and found that the flexural strength of PMMA decreased with the addition of TNPs with a gradual decline with increasing concentrations of nanoparticles. In contrast, the study by Bdelraouf et al [57] showed an increase in the FS with 5% TNPs, which may be due to the resin type used: autopolymerized resin.…”
Section: Discussionmentioning
confidence: 99%
“…(5) TiO2 NP, when added to denture base resins, showed a significant increase in certain properties, like the mechanical properties of PMMA. (15) , Hwever, on addition of these nanoparticles, the comparative effect on surface Roughness is not known.…”
Section: Discussionmentioning
confidence: 99%
“…НЧ Ag найбільш широко використовуються для модифікації матеріалів зубних протезів [31]. Їх синтезують хімічними і фізичними методами, а також за участю біологічних речовин, тобто методами «зеленого синтезу» [32], і вводять до складу протезного матеріалу [33] Добре відомо, що наносрібло має широкий спектр антибактеріальної дії [34]. Це досягається шляхом порушення проникності клітинної стінки бактерій, пошкодження ДНК та інактивації основних білків [35].…”
unclassified